OPTIMIZING PRODUCTION OF LEMURU FISH (Sardinella Longiceps) WITH HIGH FATTY - ACID OMEGA- 3 USING LIQUID SMOKED GINGER FLAVOR PROCESS - Wahyuningsih , (JOURNAL OF COASTAL DEVELOPMENT, 2005)
Lemuru Fish (Sardinella longiceps) have high enough of protein contents (17,8-20%). However, lemuru fish also contains important fatty-acid, especially omega-3. Because of the contains of fatty acid was high (1-24%) and the texture is not compact, the fish become easily be broken and become spoiled. That was because of the activity of microbes or the autolysis on the post morterm. Because of that, the right and intensive handling is needed , it can be done with immediate process or with long-lasting storage. In this research, the pickling method that used was smoking with liquid smoke. The purpose of this research is to find the optimum operation condition for liquid smoke process of fish lemuru to produce lemuru fish that its fatty-acid Omega-3 did not decomposed and the fish has unique taste. The methods of this research was completely random design with concentration of liquid-smoke as the treatment and duration of liquid-smoke as the block. The fixed variables are the weight of fish, fish thickness, temperature, salt contained and duration of measurement. The non-fixed variable is concentration of smoked-liquid. At the condition where the concentration was 6% , 25 minutes of the soaking time gave the best optimal condition which the score shown was EPA = 0.6066 g/100g ,DHA = 0.4033g/100g, TBA = 0.86 mg/kg, TVB = 4.432 mg N/100g, TMA = 5.47% mgN and the total of microorganism is 3.62 x 106 CFU.